Psychometric Analysis of a German-Language Version of the Work–Family Conflict and Family–Work Conflict Scale - Komlenac, Nikola; Stockinger, Lisa; Vogler, Tanja; Hochleitner, Margarethe (Frontiers in Psychology, 2021)
The Work–Family Conflict and Family–Work Conflict Scale (WFC & FWC Scale) is a questionnaire commonly used to assess conflicts that arise when required time devotion and strain for work obligations interfere with family responsibilities (work-family conflict) and conflicts that arise when family responsibilities interfere with work responsiblities (family-work conflict). Past reports on the psychometric properties and recommendations for application of the WFC & FWC Scale mostly rely on samples from the United States. The current study is the first to report psychometric properties of a German-language version of the WFC & FWC Scale, including invariance analyses across women and men, and test-retest reliabilities. The analysis of the latent structure that was based on responses from 274 employees (77.0% women, 23.0% men) of a medical university in Austria revealed that the bifactor model had a satisfactory fit with the data. Configural and metric invariance indicated a similar factor structure and similar meaning in women and men. However, scalar invariance cannot be assumed. Thus, differences in scale scores between women and men might not adequately reflect level differences in the underlying latent factor. High internal consistencies and high test-retest reliabilities offer evidence for adequate reliability. Additionally, evidence for convergent (links to work stress and relationship satisfaction) and divergent validity (no links to career ambition) were found. In summary, the current study offers adequate evidence for validity and reliability of a German-language version of the WFC & FWC Scale.